Concept Mapping as a Catalyst for Applied Learning and Practical Skill Development in Photosynthesis at Senior High School - Sam, Comfort Korkor; Owusu-Amponsem, George (European Scientific Journal, ESJ, 2026)
Concept mapping is recognised as an effective instructional strategy that promotes meaningful learning, particularly in science education. It facilitates planning, teaching, revision, and assessment, helping students link concepts for deeper understanding. This study investigated the impact of concept mapping on students’ performance in photosynthesis at the senior high school level in the Tolon District of Ghana. A quasi-experimental non-equivalent group design was employed involving 80 Form 3 Biology students selected using simple random sampling. The results indicated no statistically significant differences in students’ knowledge and understanding of photosynthesis (t(78) = .38, p = .702) between experimental and control groups. Regarding application of knowledge, the control group significantly outperformed the experimental group in photosynthesis (t(78) = -2.23, p = .029). The experimental group also showed superior practical skills in photosynthesis (t(78) = 4.42, p < .001). No significant gender differences were found. Based on the findings, it is recommended that concept mapping be adopted as a key instructional strategy to enhance students’ practical skills in photosynthesis.